Metaphoric language and the articulation of emotions by people affected by motor neurone disease. - Locock, L; Mazanderani, F; Powell, J (2012)
OBJECTIVE: To explore the use of metaphoric language to convey emotion in interviews with people affected by motor neurone disease, a progressive neurological condition that sits between chronic and terminal illness. METHODS: Secondary analysis of 46 interviews with people affected by motor neurone disease in the United Kingdom (35 individuals with the condition, 11 carers). RESULTS: Metaphor and figurative language was used to communicate the intensely emotional experiences of being diagnosed with and living with motor neurone disease. We focus on three pervasive themes that were threaded throughout the interviews: battling and fighting; the self under attack and journeying through a physical and emotional landscape. DISCUSSION: This secondary analysis of qualitative research interviews enriches our understanding of the articulation of emotion in motor neurone disease and adds to the literature on metaphor in chronic illness. Of particular interest is how the metaphors used contrasted with other conditions in the relative absence of metaphors of 'fighting' the disease. Furthermore, we analyse the ways in which participants used metaphors to give voice to emotions that are extremely difficult to articulate in 'literal' language, and how, in doing so, they blurred the distinction between 'physical' symptoms and 'emotional' states. Sensitivity to metaphors may help professionals communicate with people affected by motor neurone disease.